Knowledge mobilisation in sub-Saharan Africa: an impact evaluation of CPDL in improving primary school children's performance. Issue 2 (5th February 2021) - Mason, Miriam; Galloway, David
Abstract : Purpose: A non-governmental organisation (NGO) with schools in Sierra Leone prioritises admission of the most disadvantaged children but nevertheless achieves high educational and social standards. These schools were asked to provide continuing professional development and learning (CPDL) for other schools. This paper aims to report the design, development and delivery of CPDL which aimed to mobilise effective practices more widely. It also reports the design and results of an impact evaluation. Design/methodology/approach: It was recognised that CPDL delivered by foreigners would be (1) unaffordable in this impoverished West African country and (2) culturally inappropriate. It was therefore delivered by local teachers from the NGO's own schools. Most had obtained no formal teaching qualification. They were trained to collect data using a quasi-experimental design for an impact evaluation of children's attendance and literacy. A total of five schools participated in the CPDL, with ten control schools. Findings: A largely unqualified team succeeded in mobilising knowledge in the experimental schools. Children's attendance in experimental schools improved over that in control schools. Performance in literacy also improved significantly and was maintained at follow-up. Research limitations/implications: Findings of the impact evaluation are seen as indicative rather than causal because a quasi-experimental study was conducted rather than a randomised controlled trial. Originality/value: This lies in (1) teachers in schools with a severely disadvantaged intake providing a structured programme of CPDL for teachers in other schools; (2) school improvement through knowledge mobilisation in CPDL; (3) an impact evaluation with a quasi-experimental design showing improvement in children's performance.